Two diverging paths toward a common destination: The dialogism of Vygotsky and Bakhtin. (December 2019) - Eun, Barohny
A search for a distinctive human trait was a common intellectual quest during the beginning of the 20th century. Consciousness was often discussed as the unique feature of humanness and Vygotsky and Bakhtin joined in the debate with their unique contributions to understanding human consciousness. The purpose of the current paper is to present the contributions of Vygotsky and Bakhtin as grounded in the common framework of dialogism. Within this general framework of dialogism, the specific approaches each scholar undertook differ and reflect their underlying differences in worldviews. The dialogism of Vygotsky is characterized as dialectical and Bakhtin's dialogism is represented as mainly polyphonic. The diverging viewpoints within a common framework have the potential to enrich our understanding of human consciousness as they complement each other.